HAEMATOLOGICAL AND SERUM BIOCHEMICAL PARAMETERS OF YANKASA EWES FED VARYING LEVELS OF LOCALAND INDUSTRIAL SUPPLEMENTED PREMIX (American Journal of Technology and Applied Sciences, 2022)
The experiment was designed to evaluate the haematological and serum biochemical parameters of Yankasa ewe fed varying levels of local and industrial supplemented premix. The experimental design used was Complete Randomized Design (CRD), whereby twenty-five (25) Yankasa ewes were randomly allocated to five (5) treatment groups. Dietary premix of both local and industrial was administered to the animals at five (5) inclusion levels (0 as a control, local and industrial 25:75, 50:50, 75:25 and 100 % local), the feed offered and left over were recorded daily.At the beginning of the growth studies, ewes were weighed and were subsequently weighed weekly. Blood samples were collected for haematological and serum biochemistry study, three (3) Yankasa ewes were randomly picked per treatment and bled through the jugular vein and 5 ml of blood samples per each was collected out of which 3 ml were transferred into a plastic tube containing Ethylene Diamine Tetra Acetic acid (EDTA) for haematological studies; while the remaining 2 ml were emptied into another vial free of EDTA used for serum biochemical studies. All data generated in this study were subjected to Analysis of Variance (ANOVA) using the General Linear Model (GLM) procedure of SAS (2008). The results of this study shows that significant differences were not observed between the treatments in all the parameters for haematological study and the values of most parameters measured were within the normal range. All serum biochemical parameters final values are observed to be within the normal range,with the exception of creatinine final values which shows that Yankasa ewes fed with local and industrial differs significantly from those fed 0 % premix (control). It can therefore be concluded that inclusion of both local and industrial premix at 50-100 % into the diet of Yankasa ewes, does not have any negative effect on the health of the animals as values of all the haematological and serum biochemistry parameters are within the normal value.